Garlic (Allium sativum) and Amla (Emblica officinalis) Powder Addition in the Diet Affects Production Performance of White Leghorn Laying Hens - Aswal, Pooja; Kumar, Anil; Singh, Pankaj (Indian Journal of Animal Nutrition, 2017)
This study was carried out to investigate the effect of dietary supplementation of garlic (Allium sativum) and amla (Emblica officinalis) powder on egg production and egg quality in laying hens for 8 weeks (26-33 weeks of age). One hundred and twenty white leghorn layers (26 weeks of age) were divided randomly into 4 groups in a complete randomized design. Birds of control group were fed control diet while the layers of other groups were fed the control diet supplemented with amla powder (@ 5 g/kg or garlic powder (@ 2 g/kg or garlic and amla powder + garlic powder (@ 2.5 and 1 g/kg. Production performance was studied in 2 periods of 28 days each (26-29 wk and 30-33 wk). There was an increase (P<0.05) in feed intake, egg production and feed conversion ratio during period due to supplementation of garlic followed by combination of garlic and amla. The values of Hb, total erythrocyte count, total lecocyte count, PCV, serum total protein and albumin increased in response to garlic amla and both over the experimental period. The retention of CP, EE and OM increased (P<0.05). Also, there was increase in egg weight, yolk weight, egg crude protein due to supplementation of garlic in layers diet as compared to control. On the other hand, cholesterol and triglycerides levels in egg decreased (P<0.05) due to garlic powder supplementation. The values of shape index, yolk index and Haugh unit of egg were similar in all the treatments. Therefore, dietary supplementation of garlic powder @ 2 g/kg, amla powder @ 5 g/kg or their combination (amla powder @ 2.5 g and garlic powder @ 1 g/kg diet) to layer diet improved production performance, egg weight and quality of eggs in White Leghorn laying hens.